Trends in ‘Critical Thinking’ as a National Research Theme in Indonesia for the Period 2021 - 2024 - Mahir Mahir; M. A. Martawijaya; Abdul Haris (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the trend of students' critical thinking skills in national research proposals received by the Directorate of Research, Technology, and Community Service (DRTPM) in Indonesia over the past four years. Critical thinking is an essential ability in 21st-century education, which includes interpreting, analyzing, evaluating, and inferring information by students to produce solutions to real problems. Data were taken from research proposals received and approved by DRTPM from 2021 to 2024. The analysis method includes a descriptive quantitative assessment of the number of proposals that make students' critical thinking skills the central theme of education research. The study results show a significant improvement trend in the theme of students' critical thinking skills in the proposals submitted by researchers over the past four years, especially in implementing various efforts to improve students' critical thinking skills. These findings are expected to provide input for DRTPM to develop research policies and training programs to continue improving the quality of research in Indonesia.